In Vitro Study On Targeting Developmental Embryonation Pattern Of Eggs Of Ascarid Species Of Wild Animals (Applied Biological Research, 2014)
The present study was aimed to investigate the time intervals required by  the eggs of two ascarid species - Baylisascaris transfuga retrieved from  Melursus ursinus (Sloth bear), and Toxascaris leonina, retrieved from  Panthera leo persica (Asiatic/Indian lion) to reach infective stages at  controlled temperature (27±1°C) in 0.4% formalin solution as well as in  faecal samples as such. The incubated material revealed that the eggs  advanced to two-cell stage at day 2 and 3 post-incubation in case of T.  leonina and B. transfuga, respectively, in formalin solution as well as in  faecal samples. The final infective stages having 2nd stage larvae inside the  eggs were observed at day 12 and 9 post incubation in 0.4% formalin  solution and at day 14 and 9 post-incubation in faecal samples in case of B.  transfuga and T. leonina, respectively. To check the reoccurrence of  infection of these parasites having direct life cycle, better management  practices involving anthelmintic therapy of the infected individu
Keywords: Ascarids; Baylisascaris transfuga; Embryonation; Toxascaris leonina